Determinación de Factores que Afectan la Medición de los Niveles de Ruido y Aislamiento Acústico en una Cabina Insonorizada para Autopartes - Fuentes Fuentes, Jorge Mauricio (2019)
At the final vehicle testing process, car assemblers perform checks of unwanted internal noise, and then eliminate them, in order to guarantee customer satisfaction. These tests are carried out at one hundred percent of the units. The noise measurements made by the assemblers are subjective and depend on hearing ability of the inector performing the test. All the units that are detected by the client are segregated and rejected. In the event that the percentage of units that have noise levels over the customer's standard, controlled shipments can be reached, which imply additional inspections, at the supplier's expense, at their facilities. Through the use of a soundproof chamber, the detection of products that do not meet the customer's standard is performed in the supplier's own plant, without the need to mount the part with noise in the vehicle. However, in order to simulate a process similar to that in a vehicle, factors that have an impact on noise measurement must be determined. In this project, the soundproof chamber was not built, but it was simulated with a computer program and calculations with a validated mathematical model of acoustic insulation for double walls, and by using the methodology of the design of experiments, they were simulated in the software each of the factors. To determine the combination of variables, a matrix design was used, with the help of statistical software. Materials were used in the simulation, which, due to their cost, can easily be found in the Ecuadorian market, so that this device can then be used in all the production plants of auto parts, so that the noise level is validated. Finally, this methodology was used to determine the factors that influence the measurement of noise in a low-cost soundproof booth in chamber to reduce airborne noise in the measurement environment